Efektivitas Block Scheduling dengan Penemuan Terbimbing Ditinjau dari Kemampuan Pemecahan Masalah Matematis - Elvira Riska Harahap; Abdul Mujib (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
This study aims to determine the effectiveness of block scheduling with guided discovery learning on students’ mathematical problem solving. This research was conducted on class XI students at MAN 2 Deli Serdang, North Sumatra. This type of research is Mixed Method Research research with data triangulation methods, namely tests, observations and, interviews. The subjects of this study consisted of 4 people. The instruments used in this study were tests and interviews. Problem-solving abilities were obtained by tests of mathematical problem-solving abilities followed by interviews that were guided by the results of previous tests. The results showed that block scheduling with guided discovery was effective in terms of mathematical problem-solving abilities.